Tatami mat

JP7633800B2Active Publication Date: 2025-02-20SEKISUI SEIKEI LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020203455
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-08
Publication Date
2025-02-20
Estimated Expiration
2040-12-08

AI Technical Summary

Benefits of technology

【0009】 本発明の畳表の構成は上述の通りであり、クリーン性及び耐汚染性が優れている。又、難燃性、火がついても短時間で消化しうる防炎性、抗菌性等が優れている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633800000001
    Figure 0007633800000001
  • Figure 0007633800000002
    Figure 0007633800000002
  • Figure 0007633800000003
    Figure 0007633800000003
Patent Text Reader

Abstract

To provide a tatami facing exhibiting high cleanliness and contamination resistance, high fire retardancy, high flame proofness enabling extinguishing within a short time, antibacterial property, etc.SOLUTION: The tatami facing is formed by using a resin twist yarn made of 2-10 thermoplastic resin single fibers of 300-2000 denier as a warp yarn and a rush as a weft yarn. For the rush, an artificial rush is preferred, which is obtained by binding uniaxial drawing films made of olefin resins and inorganic fillers in a string shape, passing the obtained bound body through a gap of a heating member having the gap narrower than the diameter of the bound body to irregularly and partially fusing and binding the uniaxial drawing films of the bound body, and forming a fused covering on the surface of the bound body.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a tatami covering. [Background technology]

[0002] Tatami mats, which are widely used as flooring in Japanese houses, are made by laminating a tatami facing on the surface of a tatami floor. Tatami facings have been produced by weaving natural rush as the weft and cotton or hemp as the warp using a hikime weave or meseki weave technique, but natural rush has drawbacks such as insect infestation, low mechanical strength, high cost, and limited supply.

[0003] For this reason, artificial rushes made from paper or various thermoplastic resin films have recently been proposed (see, for example, Patent Documents 1, 2, and 3). These artificial rushes are industrial products made from paper and plastic resin, and therefore have the advantages of being pest-free, low-cost, stable in supply, and excellent mechanical strength and cushioning properties. Furthermore, artificial rushes have been proposed that have been coated with functional substances such as anti-mite agents, anti-mildew agents, deodorants, antibacterial agents, flame retardants, VOC adsorbents, far-infrared emitters, and negative ion emitters to improve their functionality (see, for example, Patent Document 4).

[0004] However, cotton and hemp threads are still used as warp threads. These warp threads have excellent water absorption and water retention, and tatami mats made of artificial rush made of thermoplastic resin woven as weft threads have excellent water absorption and water retention as tatami mats, despite the use of artificial rush, which has low water absorption and water retention. Therefore, when miso soup, coffee, etc. is spilled on the tatami mat, it is difficult to wipe it off, and it remains on the surface of the tatami mat for a long time or stains, which is a drawback in that it has low cleanability and stain resistance.

[0005] Furthermore, since tatami mats are a building material for houses, there has been a demand in recent years for them to have superior flame retardancy, flame resistance that allows fire to be extinguished in a short time even if it catches fire, antibacterial properties, and other properties. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 8-170422 [Patent Document 2] JP 2014-95187 A [Patent Document 3] Japanese Patent Application Publication No. 1-92443 [Patent Document 4] JP 2005-282152 A Summary of the Invention [Problem to be solved by the invention]

[0007] In view of the above problems, the object of the present invention is to provide a tatami surface that is excellent in cleanability and stain resistance. Another object is to provide a tatami surface that is excellent in flame retardancy, flame resistance that allows fire to be extinguished in a short time even if it catches fire, antibacterial properties, etc. [Means for solving the problem]

[0008] That is, the present invention provides: [1] A tatami mat woven using a resin-based twisted yarn formed by twisting 2 to 10 thermoplastic resin single fibers having a denier of 300 to 2000 as a warp thread and rush as a weft thread, [2] The tatami covering according to [1] above, characterized in that the thermoplastic resin is a polypropylene-based resin or a polyester-based resin. [3] The tatami mat according to [1] or [2] above, characterized in that a flame retardant and / or an antibacterial agent is further kneaded into the thermoplastic resin monofilament. [4] The tatami mat according to any one of the above [1] to [3], characterized in that the rush is artificial rush. [5] The tatami covering described in [4] above, characterized in that the artificial rush is obtained by bundling uniaxially oriented films made of olefin resin and inorganic filler into a string shape, and passing the resulting bundle through a gap in a heating element having a gap narrower than the diameter of the bundle, thereby irregularly and partially fusing and binding the uniaxially oriented films of the bundle and forming a fused coating on the surface of the bundle; and [6] The tatami mat according to [5] above, further comprising a flame retardant and / or an antibacterial agent kneaded into the uniaxially stretched film. Regarding. Effect of the Invention

[0009] The tatami mat of the present invention has the above-mentioned structure, and is excellent in cleanability and stain resistance. It also has excellent flame retardancy, flame resistance that allows fire to be extinguished in a short time even if it catches fire, antibacterial properties, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The tatami covering of the present invention is characterized in that it is woven using resin-based twisted yarns formed by twisting 2 to 10 thermoplastic resin monofilaments having a denier of 300 to 2000 as warp yarns and rush as weft yarns.

[0011] The thermoplastic resin may be any resin having thermoplastic properties. Examples of the thermoplastic resin include polypropylene resins such as polypropylene resin and ethylene-propylene copolymer, ethylene resins such as high-density polyethylene resin, medium-density polyethylene resin, low-density polyethylene resin, linear low-density polyethylene resin, ethylene-1-butene copolymer, ethylene-1-pentene copolymer, and ethylene-1-hexene copolymer, other olefin resins, polyester resins, acrylic resins, and urethane resins. Polypropylene resins and polyester resins are preferred.

[0012] The resin twisted yarn is a resin twisted yarn made by twisting thermoplastic resin monofilaments, and the thermoplastic resin monofilaments are simply thread-like fibers extruded from a thermoplastic resin. If the thickness of the thermoplastic resin monofilaments is thin, the amount of water absorbed and retained during twisting increases, and if miso soup, coffee, or the like is spilled and left for a long time, the resin twisted yarn is impregnated with the liquid, which cannot be easily wiped off, and the cleanability and stain resistance decrease. Also, if the thickness is thick, it becomes difficult to twist and the twisted resin twisted yarn becomes thick, making it impossible to use as a warp thread for tatami mats, so the denier is 300 to 2000.

[0013] If the number of twisted thermoplastic resin single fibers is small, the mechanical strength is decreased, and if the number is large, if miso soup, coffee, etc. is spilled on the twisted resin-based twisted yarn and left for a long time, the resin-based twisted yarn is impregnated with the spilled liquid and cannot be easily wiped off, and the cleanability and stain resistance are reduced, and the yarn becomes too thick, making it difficult to weave and unable to be used as the warp thread for tatami mat facings. Therefore, the number of twisted thermoplastic resin single fibers is 2 to 10, preferably 3 to 5. The thickness of the resin-based twisted yarn is not particularly limited, but since it is the warp thread for tatami mat facings, it is preferably 1000 to 5000 denier.

[0014] The resin-based twisted yarn obtained by twisting the above-mentioned thermoplastic resin monofilaments means a resin-based twisted yarn obtained by twisting only a plurality of thermoplastic resin monofilaments, and does not include a mixed twisted yarn obtained by mixing and twisting natural yarns such as cotton yarn and hemp yarn.

[0015] Since tatami mats are building materials for houses, it is preferable that they have excellent flame retardancy and flame resistance that allows the fire to be extinguished in a short time even if it catches fire. Since the tatami mats of the present invention are woven using rush grass as the weft and the above-mentioned resin-based twisted yarn as the warp, in order to improve the flame retardancy and flame resistance of the tatami mats, it is preferable that the warp threads melt and the weft threads break apart when the tatami mats catch fire or are exposed to high temperatures. This is because when the weft threads break apart, gaps are generated between the weft threads, preventing the fire from spreading and allowing the fire to be extinguished.

[0016] Therefore, when the resin twist yarn shrinks after being melted and cut or at the same time, gaps are formed above and below the cut surface of the resin twist yarn, and the weft yarn located at the cut surface is pulled above and below the cut surface as the resin twist yarn melts and forms gaps above and below. Therefore, it is preferable that the resin twist yarn has heat shrinkability, and the heat shrinkage rate is preferably 3% or more.

[0017] The heat shrinkage rate is the shrinkage ratio when the resin twisted yarn is heated in an atmosphere of 60°C for 6 hours without load, and is calculated by the following formula. Heat shrinkage rate (%) = (length of resin-based twisted yarn before heating - length of resin-based twisted yarn after heating) x 100 / length of resin-based twisted yarn before heating

[0018] The method for imparting heat shrinkability to the resin-based twisted yarn may be any conventionally known method, such as uniaxially stretching a thermoplastic resin monofilament before twisting.

[0019] It is preferable to add a flame retardant and / or an antibacterial agent to the thermoplastic resin monofilament in order to improve the flame retardancy of the tatami mat covering, the flame resistance so that even if a fire is started, the fire can be extinguished in a short time, the antibacterial properties, etc. Also, since the flame retardant and / or the antibacterial agent is peeled off and removed over time and its effectiveness is reduced if it is applied to the surface of the thermoplastic resin monofilament, it is preferable to knead it into the thermoplastic resin monofilament.

[0020] As the flame retardant, any known flame retardant that has conventionally been used in the molding of thermoplastic resin molded products can be used. Examples of the flame retardant include graphite-based flame retardants, nitrogen-based flame retardants such as melamine-based compounds and guanidine-based compounds, red phosphorus-based flame retardants, phosphorus-based flame retardants such as ammonium phosphate, silicon-based flame retardants, and bromine-based flame retardants, with bromine-based flame retardants being preferred.

[0021] As the antibacterial agent, any conventionally known antibacterial agent can be used, and examples thereof include inorganic metal ion compounds in which antibacterial metals (e.g., silver, zinc, copper, etc.) or metal ions are supported on an inorganic carrier (e.g., trade name "Novalon" manufactured by Toa Gosei Co., Ltd.), nitrile compounds, pyridine compounds, haloalkylthio compounds, organic iodine compounds, thiazole compounds, benzimidazole compounds, wasabi components (allyl isothiocyanate), and the like are listed, and zinc-based metal ion compounds are preferred.

[0022] Furthermore, if necessary, an anti-mite agent, an anti-fungal agent, a deodorant, an inorganic filler, a colorant, etc. may be kneaded into the thermoplastic resin monofilament.

[0023] Examples of the anti-mite agents include pyrethroid compounds, organophosphorus compounds, carbamate compounds, etc., while examples of the anti-fungal agents include natural products such as persimmon tannin, wood vinegar, cypress essential oil, Japanese cedar essential oil, wasabi, catechin, wood vinegar, etc., organic compounds such as thiabendazole, diphenyl, orthophenylphenol, and inorganic compounds such as titanium oxide, etc., and examples of the deodorizers include carbon materials such as charcoal, bamboo charcoal, activated charcoal, binchotan charcoal, etc., silica, alumina, zeolite, etc.

[0024] Examples of the inorganic filler include calcium carbonate, magnesium carbonate, aluminum oxide, magnesium oxide, titanium oxide, magnesium hydroxide, talc, mica, and clay.

[0025] Examples of the colorant include organic pigments such as azo pigments, phthalocyanine pigments, threne pigments, and dye lake pigments, and inorganic pigments such as oxide pigments, molybdenum chromate pigments, sulfide / selenide pigments, and ferrocyanide pigments.

[0026] Furthermore, if necessary, antioxidants such as phenol-based antioxidants and aromatic amine-based antioxidants, ultraviolet absorbers such as salicylic acid ester-based, benzophenone-based, benzotriazole-based and cyanoacrylate-based ultraviolet absorbing agents, hindered amine-based light stabilizers, antistatic agents such as cationic and nonionic types, impact modifiers, etc. may be kneaded into the composition.

[0027] The rush may be natural rush or artificial rush made from paper or thermoplastic resin. However, artificial rush is preferred, which is obtained by bundling uniaxially oriented film made of olefin resin and inorganic filler into a string shape and passing the bundle through a gap in a heating element having a gap narrower than the diameter of the bundle, thereby irregularly and partially fusing and bundling the uniaxially oriented films of the bundle and forming a fused coating on the surface of the bundle.

[0028] The thickness of the rush is not particularly limited, but is generally 0.5 to 5 mm in diameter, preferably 0.8 to 3 mm. Furthermore, when artificial rush is dense, it becomes heavy and hard, and its heat insulation, impact resistance, shielding properties, etc. decrease, so it is preferable for it to have a porosity of 15 to 50%.

[0029] The porosity is the volume ratio of air bubbles that are present in the artificial rush. The air bubbles may be not only closed bubbles but also open bubbles, and the open bubbles may be connected to the outside of the artificial rush.

[0030] The uniaxially stretched film is a film obtained by uniaxially stretching a resin film made of an olefin resin and an inorganic filler.

[0031] Examples of the olefin resin include high-density polyethylene resin, medium-density polyethylene resin, low-density polyethylene resin, linear low-density polyethylene resin, polypropylene resin, ethylene-propylene copolymer, ethylene-1-butene copolymer, ethylene-1-pentene copolymer, ethylene-1-hexene copolymer, and the like, with high-density polyethylene resin and polypropylene resin being preferred.

[0032] Examples of the inorganic filler include calcium carbonate, magnesium carbonate, aluminum oxide, magnesium oxide, titanium oxide, magnesium hydroxide, talc, mica, and clay.

[0033] If an inorganic filler is contained in a resin film, when the resin film is uniaxially stretched, voids are formed in the uniaxially stretched film with the inorganic filler as a nucleus, making the film lighter and improving its heat insulation and cushioning properties, etc., so it is preferable to add 10 to 50 parts by weight of an inorganic filler to 100 parts by weight of the thermoplastic resin.

[0034] In addition, it is preferable to add a flame retardant and / or an antibacterial agent to the resin film in order to improve the flame retardancy of the tatami mat surface, the flame resistance that allows fire to be extinguished in a short time even if it catches fire, the antibacterial properties, etc. If the flame retardant and / or antibacterial agent is applied to the surface of the thermoplastic resin monofilament, the agent will peel off and be removed over time, reducing the effectiveness, so it is preferable that the agent is kneaded into the resin film.

[0035] The flame retardant and antibacterial agent are as described above, and further, the above-mentioned anti-mite agent, anti-fungal agent, deodorant, colorant, etc. may be kneaded in as required.

[0036] The resin film can be produced by any conventionally known production method, for example, a film-forming method such as an extrusion method, a T-die method, a casting method, a calendar method, an inflation method, or a press method using a resin composition comprising the olefin-based resin and an inorganic filler.

[0037] The uniaxially stretched film is obtained by uniaxially stretching the resin film. Any conventionally known method may be used as the uniaxial stretching method, and examples of the method include a roll uniaxial stretching method and a zone uniaxial stretching method.

[0038] If the uniaxial stretching temperature is low, the resin film cannot be stretched uniformly, and if it is high, the resin film will melt and break. Therefore, the temperature is preferably in the range of "melting point -60°C" to the melting point of the olefin resin of the resin film to be stretched, and more preferably "melting point -50°C" to "melting point -5°C" of the olefin resin.

[0039] The uniaxial stretching ratio is preferably 2 to 10, since a lower ratio reduces the mechanical strength, and a higher ratio makes the film hard and reduces the texture of the rush. The thickness of the uniaxially stretched film is preferably 5 to 20 μm.

[0040] The bundle is formed by bundling the uniaxially stretched film into a string shape. The bundling method is not particularly limited, and examples thereof include a method of folding the uniaxially stretched film along the uniaxial stretching direction and bundling it, a method of twisting narrow uniaxially stretched films into a twisted thread shape, and a method of combining narrow uniaxially stretched films into a braided string shape, and the folding and bundling method is preferred.

[0041] Next, the bundle is passed through the gap of a heating element having a gap narrower than the diameter of the bundle, whereby the uniaxially oriented films are irregularly fused and converged together and a fused coating is formed on the surface, thereby obtaining artificial rush.

[0042] The heating member may be any one that can be heated, has a narrow gap that is narrower than the diameter of the bundle, and allows the bundle to pass through, but since the bundle is passed through the narrow gap to irregularly fuse and converge the uniaxially stretched films to each other and form a fused coating on the surface, the diameter of the gap is preferably 40 to 90% of the diameter of the bundle. The cross-sectional shape of the gap may be approximately the same as the cross-sectional shape of the artificial rush to be obtained, and is preferably, for example, circular, elliptical, rectangular, hexagonal, octagonal, etc.

[0043] Furthermore, protrusions may be formed near the exit of the gap so as to form wrinkles or through-holes in the formed fusion coating. When through-holes are formed in the formed fusion coating, the gaps in the fusion coating are communicated with the outside air, which is preferable as it further improves moisture absorption, heat insulation, etc.

[0044] The heating temperature of the heating element is higher than the melting point of the olefin resin of the uniaxially stretched film, and preferably is between "melting point + 100°C" and "melting point + 150°C" of the olefin resin, since the uniaxially stretched films are irregularly fused and bound together by passing the bound material through the gap of the heating element and a fused coating is formed on the surface.

[0045] If the speed at which the bundle is passed through the gap of the heating element is slow, the fusion rate of the uniaxially stretched film will increase, the void ratio will decrease, and the bundle will become heavier and harder. Conversely, if the speed is fast, it will become difficult to form a fused coating on the surface. Therefore, although it depends on the heating temperature, a speed of 15 to 75 m / min is generally preferred.

[0046] The tatami mat of the present invention is woven using the above-mentioned resin-based twisted yarn as the warp and rush as the weft, but the weaving method is not particularly limited and any conventionally known weaving method can be used, such as hikime weave, meseki weave, plain weave, and twill weave.

[0047] In addition, in order to improve the mechanical strength of the tatami mat, adjacent rushes are woven in close contact with each other, and adjacent warp threads are preferably woven at intervals of 2 to 30 mm, as in conventional tatami mats. EXAMPLES

[0048] Next, examples of the present invention will be described, but the present invention is not limited to these examples.

[0049] Manufacturing of thermoplastic resin monofilaments The amount of polypropylene resin (density 0.9 g / cm) shown in Table 1 3 A resin composition consisting of terbium phosphate (melting point 155-165°C), polyester resin, a bromine-based flame retardant (manufactured by Dainichiseika Chemicals Mfg. Co., Ltd., product name "Daifuunen") and a zinc-based antibacterial agent (manufactured by Toa Gosei Co., Ltd., product name "Novalon") was fed to a single-screw kneading extruder and melt-kneaded and extruded at 210°C to obtain thermoplastic resin single fibers (1), (2), (3) and (4) having the deniers shown in Table 1.

[0050] [Table 1]

[0051] Manufacturing of resin-based twisted yarn Five each of the thermoplastic resin monofilaments (1), (2), (3) and (4) were bundled and twisted to obtain 2500 denier resin twisted yarns (1) and (2) and 5000 denier resin twisted yarns (3) and (4). Also, two resin twisted yarns (1) and three 550 denier cotton yarns were bundled and twisted to obtain a 2650 denier mixed twisted yarn.

[0052] Water absorption and retention test for twisted yarn The resin-based twisted yarns (1) and (4) and the mixed twisted yarn, each having a length of 10 m, were conditioned for at least 2 hours in an atmosphere at 25°C and 50% humidity, and then immersed in water for 1 hour. After immersion, the yarns were removed and dried in an atmosphere at 25°C and 50% humidity, and the weight of the twisted yarn was measured at each of the prescribed drying times shown in Table 2, and the results are shown in Table 2. The weight of the twisted yarn before immersion in water was set to 0, and the weight increase rate of the twisted yarn at each of the prescribed drying times was shown in %.

[0053] Heat shrinkage rate The obtained resin-based twisted yarns (1) and (4) and the mixed twisted yarn, each having a length of 10 cm, were fed into a gear oven set at 60° C. and heated for 6 hours without load to measure the heat shrinkage. The results are shown in Table 2.

[0054] [Table 2]

[0055] (Examples 1 to 4, Comparative Examples 1 and 2) Manufacturing of artificial rush Polypropylene resin (density 0.9g / cm 3A resin composition consisting of 100 parts by weight of terbium phosphate (melting point 155-165°C), 27 parts by weight of calcium carbonate, 2.0 parts by weight of an azo-based inorganic pigment, and the specified amounts of a bromine-based flame retardant (manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., product name "Daifuunen") and a zinc-based antibacterial agent (manufactured by Toa Gosei Co., Ltd., product name "Novalon") shown in Table 3 was supplied to a single-screw kneading extruder with a 70 mm screw and kneaded and extruded at 210°C to obtain a polypropylene resin film having a thickness of 100 μm.

[0056] The obtained polypropylene resin film was fed to a hot plate type uniaxial stretching device set at 120°C and stretched 5 times to obtain a uniaxially stretched film with a thickness of 20 μm. The obtained uniaxially stretched film was folded in the uniaxial stretching direction and passed through a through hole with a diameter of 2.0 mm to obtain a bundle formed into a string shape with a diameter of 2.0 mm. The obtained bundle with a diameter of 2.0 mm was fed to a heating element having a circular cross-sectional gap with a diameter of 1.0 mm, and passed through the gap at a speed of 65 m / min to obtain artificial rush (1), (2), (3) and (4).

[0057] The heating element was heated to 300°C, and eight pointed protrusions with a height of 0.05 mm were installed at 45° intervals near the exit of the gap. The obtained artificial rush had the tape-shaped body partially fused and a fused coating formed on the surface, with random through holes and unevenness formed in the fused coating. The obtained artificial rush was black, had a diameter of about 1.1 mm, and a porosity of 33%. The mechanical properties of artificial rushes (1), (2), (3), and (4) were measured in accordance with JIS K7127 at a chuck distance of 200 mm and a tensile speed of 300 mm / min, and the breaking strength in the longitudinal direction was 9.5 to 9.8 N, and the breaking elongation was 9 to 11%.

[0058] [Table 3]

[0059] Manufacturing of tatami mats The specified artificial rush shown in Tables 4 and 5 was used as the weft, twisted yarn was used as the warp, the warp interval was set to 4 mm, and the weft thread count was set to 90 threads / 10 cm. The tatami mat was obtained by weaving using the specified weaving method shown in Tables 4 and 5.

[0060] In addition, in Comparative Example 2, natural rush was used as the weft, the resin-based twisted yarn (2) was used as the warp, the interval between the warp threads was set to 4 mm, and the weft thread count was set to 90 threads / 10 cm. A tatami mat was obtained by weaving with a hijime weave.

[0061] The obtained tatami surface was cut into three samples, which were then subjected to a combustion test in accordance with Article 4 "Carpets" of the Fire Service Act Enforcement Regulations, to measure the afterflame time and char length, with the results shown in Tables 4 and 5. Also, samples with an afterflame time of 20 seconds or less and a char length of 10 cm or less were given an overall rating of ○, and samples with even one point exceeding this rating were given an ×.

[0062] In addition, the antibacterial properties were evaluated according to JIS Z2801-2012, and when the antibacterial activity value was 2.0 or more, it was marked as ◯, and when it was less than that, it was marked as ×. The results are shown in Tables 4 and 5. The results are shown in Tables 4 and 5.

[0063] [Table 4]

[0064] [Table 5]

[0065] The tatami mat coverings obtained in Examples 1 and 4 and Comparative Examples 1 and 2 were cut into square samples of 10 x 10 cm, and water absorption and water retention tests were carried out in the same manner as in the water absorption and water retention test of the twisted yarn, and the results are shown in Table 5.

[0066] [Table 6] [Industrial Applicability]

[0067] The tatami mat of the present invention has excellent cleanability and stain resistance, and can be appropriately imparted with flame retardancy, flame resistance that allows fire to be extinguished in a short time even if it catches fire, antibacterial properties, etc., and can therefore be suitably used as a building material.

Claims

1. The tatami covering is woven using a resin-based twisted yarn formed by twisting 3 to 5 thermoplastic resin single fibers having a denier of 500 to 1000 as a warp yarn and an artificial rush as a weft yarn, and is characterized in that the heat shrinkage rate of the resin-based twisted yarn calculated by the following formula is 3% or more. The heat shrinkage rate is the shrinkage ratio when the resin twisted yarn is heated in an atmosphere of 60° C. for 6 hours without load. Heat shrinkage rate (%) = (length of resin-based twisted yarn before heating - length of resin-based twisted yarn after heating) x 100 / (length of resin-based twisted yarn before heating)

2. 2. The tatami mat according to claim 1, wherein the thermoplastic resin is a polypropylene-based resin or a polyester-based resin.

3. 3. The tatami mat according to claim 1, wherein a flame retardant and / or an antibacterial agent is kneaded into the thermoplastic resin monofilament.

4. The tatami covering of claim 3, characterized in that the artificial rush is obtained by bundling uniaxially oriented film made of an olefin resin and an inorganic filler into a string shape, and passing the resulting bundle through a gap of a heating element having a gap narrower than the diameter of the bundle, thereby irregularly and partially fusing and binding the uniaxially oriented film of the bundle to each other and forming a fused coating on the surface of the bundle.

5. 5. The tatami mat according to claim 4, wherein a flame retardant and / or an antibacterial agent is further kneaded into the uniaxially stretched film.

Citation Information

Patent Citations

  • JP1971-039140B

  • Simulated rash and fabric

    JP1989092443A

  • Warp for tatami facing

    JP1991180532A

  • Tatami facing

    JP1996170422A

  • Multiple rush and artificial tatami mat surface

    JP1996284039A